STUDY OF ACTION OF SPEAKING IN DISCUSSION OF THE SERAMBI INDONESIA NEWSPAPER RUBRIC, OCTOBER 2021 EDITION - Nurlaili Nurlaili; Amirzan Amirzan; Husnatun Zahara (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
There are two purposes of this research. 1) Describe the locutionary, illocutionary, and perlocutionary speech acts in the October 2021 edition of Serambi Indonesia Newspaper rubric discourse. 2) Describe the functions of locutionary, illocutionary, and perlocutionary speech acts in the October 2021 edition of Serambi Indonesia Newspaper rubric discourse. The object of research in this thesis in the form of locutionary, illocutionary, and perlocutionary speech acts contained in the discourse of the October 2021 edition of the Serambi Indonesia newspaper. The data collection techniques in this study used documentation methods and note-taking techniques. The data analysis technique used is the equivalent method. Based on the results of data analysis can be keywords. 1) The types of speech acts contained in the rubric of Serambi Indonesia Newspaper October 2021 edition found three types of speech acts, namely, locutionary speech acts, illocutionary acts, and perlocutions. 2) The function of speech acts contained in the rubric of the Serambi Indonesia newspaper, October 2021 edition, found five functions of speech acts, namely: 1) Assertive functions include asserting, expressing opinions, and describing. 2) The directive function includes inviting, asking, ordering, and ordering. 3) The commissive function includes lending and associating. 4) Expressive function of saying thank you. 5) Declarative functions change state. 2) The function of speech acts contained in the rubric of the Serambi Indonesia newspaper, October 2021 edition, found five functions of speech acts, namely: 1) Assertive functions include asserting, expressing opinions, and describing. 2) The directive function includes inviting, asking, ordering, and ordering. 3) The commissive function includes lending and associating. 4) Expressive function of saying thank you. 5) Declarative functions change state. 2) The function of speech acts contained in the rubric of the Serambi Indonesia newspaper, October 2021 edition, found five functions of speech acts, namely: 1) Assertive functions include asserting, expressing opinions, and describing. 2) The directive function includes inviting, asking, ordering, and ordering. 3) The commissive function includes lending and associating. 4) Expressive function of saying thank you. 5) Declarative functions change state.Keywords: rubric, speech act, discourse